Paradigms, paradoxes and a propitious niche: conservation and Indigenous social justice policy in Australia. Issue 5 (3rd May 2016) - Moorcroft, Heather
Abstract : In Australia, redressing past injustices and recognising Indigenous peoples' spiritual and cultural connections to land have resulted in the return of significant amounts of land to Indigenous people. Parallel to this, in attempts to address declining biodiversity, innovative and neo-liberal approaches to conservation under a new paradigm have been promoted. The role and influence of the non-state sector are increasing, and Indigenous peoples' involvement in conservation is also growing. This paper reviews the history of conservation and Indigenous social justice policy in Australia. It describes how the social justice agenda has been the primary motivator of returning land to Indigenous Australians, and historically has been the driver and catalyst for Indigenous peoples' involvement in conservation, whilst the conservation agenda has increased conservation on private lands and the role and influence of the non-state conservation sector. The paper reveals how the trajectories of conservation and Indigenous social justice have become intrinsically linked with the emergence of new paradigms, providing opportunities for a propitious niche. Yet it also shows how the two trajectories have manifested themselves with a paradox of disparity; achievements secured under an Indigenous social justice agenda are being enjoyed by conservation under the new paradigm, whilst Indigenous social justice is increasingly becoming dependent on a conservation agenda.